Shivering in Acutely Ill Vulnerable Populations - Holtzclaw, Barbara J. (AACN Advanced Critical Care, 2004)
The hazards of thermoregulatory shivering in the critically ill are often overlooked by caregivers. Shivering may accompany heat loss from bathing, dressing, transport, and many therapeutic activities. Febrile shivering is common during chills of fever, blood product transfusions, administration of antigenic drugs, and chemotherapy. Many patients are at risk for shivering and its negative consequences that increase oxygen expenditure and cardiorespiratory effort. Learning how underlying thermoregulatory mechanisms are involved in shivering clarifies how temperature gradients and environmental stimuli induce the shivering response. Knowledge of the anatomical progression of shivering equips the nurse to recognize or prevent this energy-consuming response. This article discusses measures to prevent shivering as well as evidence-based interventions to manage shivering during fever, aggressive cooling, and postoperative recovery. Detailed information is presented on assessment and documentation of the extent and severity of shivering.